2015
DOI: 10.1063/1.4921170
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced spectroscopic gas sensors using in-situ grown carbon nanotubes

Abstract: In this letter we present a fully complementary-metal-oxide-semiconductor (CMOS) compatible microelectromechanical system (MEMS) thermopile infrared (IR) detector employing vertically aligned multi-walled carbon nanotubes (CNT) as an advanced nano-engineered radiation absorbing material. The detector was fabricated using a commercial silicon-on-insulator (SOI) process with tungsten metallization; comprising a silicon thermopile and a tungsten resistive micro-heater, both embedded within a dielectric membrane f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Functionalization of carbon nanostructures changes their mechanical, structural and solubility properties. As a result, novel materials are obtained with improved processability, necessary for building molecular devices suitable for constitution of electronic systems, 1,2 gases sensors and storage, 3,4 heavy metal and nano-metallic particulate selective adsorption devices 5,6 and also drug delivery systems. [7][8][9][10] The functionalization is made through physical 11,12 or chemical routes, 13,14 doping with different atoms 15 and oxidation reactions [16][17][18][19][20][21][22] of the nanostructure surface.…”
Section: Introductionmentioning
confidence: 99%
“…Functionalization of carbon nanostructures changes their mechanical, structural and solubility properties. As a result, novel materials are obtained with improved processability, necessary for building molecular devices suitable for constitution of electronic systems, 1,2 gases sensors and storage, 3,4 heavy metal and nano-metallic particulate selective adsorption devices 5,6 and also drug delivery systems. [7][8][9][10] The functionalization is made through physical 11,12 or chemical routes, 13,14 doping with different atoms 15 and oxidation reactions [16][17][18][19][20][21][22] of the nanostructure surface.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, for CO2 breath analysis, the level of CO2 is in the range of 4 to 5 %, thus the CO2 concentration can be measured with relative short paths lengths. It has previously been reported path lengths of 10 mm or lower and up to 10 cm have been used for CO2 detection in the concentrations expected on breath [32,33]. Preliminary experiments, with a stable 80 mm path length (in an aluminium chamber shown in Figure 3) were performed to provide a stable benchmark standard.…”
Section: Sensor Chamber Designmentioning
confidence: 99%
“…CMOS integrated MIR emitters, with drive and temperature control, can feature membrane diameters as small as 600 μm, and have ∼50 mW DC power consumption (∼1 mW optical output power), when operated at 550 C, with good emission for λ > 8 μm (Figure 4a). We have also showed that the radiation properties of carbon nanotubes (CNTs) can significantly enhance both emissivity [95] and absorptivity [94] of MIR devices, due to their blackbody-like behaviour (nearly unity) (Figure 4b).…”
Section: Path To Miniaturization and Integrationmentioning
confidence: 99%